Programy wspierania rozwoju lokalnej przedsiębiorczości - studium przypadku - Filipiak, Beata (Supporting Programme of Local Activity Development - Case Study, 2007)
The article presents problems of preparing the local activity programme. The author discusses the influence of state and local aid on local activity. The author analyzes the model of state aid, state and bol law and the choice indicators for the way of development. The last past of the article, presents Goleniów case study and a proposal of new way in creating the local aid.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 434-443